2013
DOI: 10.1155/2013/724592
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antiphosphatidylserine/Prothrombin Antibodies and Their Potential Diagnostic Value

Abstract: Antiprothrombin antibodies, measured with phosphatidylserine/prothrombin complex (aPS/PT) ELISA, have been reported to be associated with antiphospholipid syndrome (APS). They are currently being evaluated as a potential classification criterion for this autoimmune disease, characterized by thromboses and obstetric complications. Given the present lack of clinically useful tests for the accurate diagnosis of APS, we aimed to evaluate in-house and commercial assays for determination of aPS/PT as a potential ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 33 publications
(45 reference statements)
3
37
1
Order By: Relevance
“…22,23 Many reports have shown the clinical utility of aPS/PT in the diagnosis of APS. 5,[24][25][26][27] In a large cohort of Japanese patients with systemic autoimmune diseases, the presence of aPS/PT significantly correlated with LA and with the clinical manifestations of APS. 5 Furthermore, aPS/PT appeared as the strongest independent risk factor for obstetric complications.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Many reports have shown the clinical utility of aPS/PT in the diagnosis of APS. 5,[24][25][26][27] In a large cohort of Japanese patients with systemic autoimmune diseases, the presence of aPS/PT significantly correlated with LA and with the clinical manifestations of APS. 5 Furthermore, aPS/PT appeared as the strongest independent risk factor for obstetric complications.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, antibodies against prothrombin, specifically aPS/PT were recognized to be importantly associated with clinical manifestations of APS [20][21][22][23]28]. In our previous study we have reported that aPS/PT of IgG and IgM isotype are strongly associated with adverse pregnancy outcome, irrespective of other antiphospholipid antibodies [22], and that their detection is particularly important for evaluation of obstetric APS.…”
Section: Discussionmentioning
confidence: 99%
“…Although antiprothrombin antibodies have not yet been included in the classification criteria of APS, they are emerging as an increasingly important supportive marker [1,[19][20][21]. We have previously reported of IgG and/or IgM antibodies against complex phosphatidylserine/prothrombin (aPS/PT) exhibiting the highest percentage of LA activity, as compared to aCL or anti-β2GPI [19] and their strong association to thrombosis and adverse pregnancy outcome, irrespective of other antiphospholipid antibodies [20,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early data from Atsumi et al showed that the presence of aPS/PT conferred an odds ratio for APS of 3.6 in his large cohort of 265 Japanese patients with systemic autoimmune diseases [10]. Recently, Zigon et al showed aPS/PT as the strongest independent risk factor for the presence of obstetric complications in a cohort of 156 patients with systemic autoimmune diseases [37]. Interestingly, while some studies support the association of aPS/PT with arterial thrombosis, mainly in the setting of ischemic/thrombotic cerebrovascular events [38,39] When systematically reviewing the topic [33••], we found 7 studies that directly compared aPT and aPS/PT and their OR for thrombosis in 1196 patients [5,9,[41][42][43][44].…”
Section: Clinical Significancementioning
confidence: 99%